Application of gravity and remote sensing data to groundwater potential in Wadi Ar-Ramah, Saudi Arabia - Mohamed, Ahmed; Alshehri, Fahad (Frontiers in Earth Science, 2023)
Water scarcity is developing in the Middle East as a result of the region’s growing population and tremendously advanced agricultural and industrial sectors. Saudi Arabia is the Middle East country with the highest water consumption, so there is an urgent need to take action, and new technology advancements in geophysical measurements allow for the monitoring of groundwater. Wadi Ar-Ramah is one region that has witnessed significant agricultural expansion as well as a serious over-exploitation of the groundwater resources that are available there. Depletion rate in groundwater of the Wadi Ar-Ramah basin at eastern Saudi Arabia was determined for the time interval of 04/2002 to 12/2021 using a combination of gravity data from the Gravity Recovery and Climate Experiment (GRACE) mission and results of land surface models. The findings are: 1) the average yearly rainfall rate was computed at 87.7 mm yr−1 over the Wadi Ar-Ramah; 2) the terrestrial water storage variation (ΔTWS) was computed at −1.216 ± 0.013 cm yr−1; 3) the GLDAS-derived soil moisture (ΔSMS) was minimal at −0.32 ± 0.025 mm yr−1; 4) the GRACE-derievd groundwater decreasing rate was calculated at 1.212 ± 0.012 cm yr−1; 5) the relief of the ground surface is producing northeasterly streams that carry the minimal surface water to the east; 6) our integrated method provides a repeatable and cost-effective approach.